Β-hydroxybutyrate (β-HB) exerts anti-inflammatory and antioxidant effects in lipopolysaccharide (LPS)-stimulated macrophages in Liza haematocheila. Issue 107 (December 2020) - Qiao, Guo; Lv, Tingli; Zhang, Mingming; Chen, Peng; Sun, Qirui; Zhang, Jialin; Li, Qiang
Abstract: Poly-β-hydroxybutyrate (PHB) can be hydrolyzed to β-hydroxybutyrate (β-HB) in the intestinal tract of animals, and dietary PHB supplementation could enhance the immunity and disease resistance of aquatic animals. Antioxidant system is responsive to PHB stimuli via MAPK/PI3K-Akt/TNF/NF-κB/TCR/TLR signaling pathways. However, the precise immunopotentiation mechanism needs further study. In this study, macrophages from spleen in Liza haematocheila was used to study the effect of β-HB on cell viability and antioxidant function to illustrate the immunopotentiation mechanism of PHB. The results showed that β-HB (100 μg/mL) promoted the viability of macrophages and balanced the production of reactive oxygen species, but inhibited the excessive production of intracellular nitric oxide. In order to further explore the immunopotentiation mechanism of β-HB, LPS (100 μg/mL) was used to induce the inflammation and investigated the inhibitory effect of β-HB on inflammation. The results showed that LPS could induce inflammation successfully, and β-HB exerted anti-inflammatory and antioxidant effects in LPS-stimulated macrophages. Compared with LPS stimuli alone, the expression of anti-inflammatory genes NF-κBIA, MAP3K8 and TLR5 in β-HB pretreatment group was up-regulated, and the expression of pro-inflammatory genes TNFSF6, TNF-α, PI3K, NF-κB and TLR1 down-regulated. It suggested that β-HB inhibited the inflammatory response by up-regulation of anti-inflammatory genes such as NF-κBIA, thereby enhancing the immunity of the body. Highlights: β-HB (100 µg/mL) promoted viability of macrophages. β-HB inhibited the excessive production of intracellular NO. β-HB inhibited LPS-induced inflammation through balance between pro-inflammatory and anti-inflammatory genes.